2006
DOI: 10.1007/s11187-006-6712-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Enhancing Workers’ Employability on Small and Medium Enterprises: Evidence from Spain

Abstract: In this paper, we analyse the effect of promoting workers’ employability on labour productivity. To this end, we adapt a simple efficiency-wage model that includes the employer’s decision on the provision of opportunities for enhancing workers’ employment prospects in a context of job insecurity. We show that (i) by facilitating workers’ employability, the firm increases its labour productivity; and (ii) the higher the job uncertainty the higher the productivity gains due to the increase in employability. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 24 publications
1
33
0
5
Order By: Relevance
“…One of the consequences of these changes is the undermined credibility of an employment model organized around the stability of the long-term relationship between employee and employer (Arocena, Nu´-n˜ez and Villanueva, 2007). Consequently, nowadays we frequently find stable and precarious employment in the same organization (Godin and Kittel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…One of the consequences of these changes is the undermined credibility of an employment model organized around the stability of the long-term relationship between employee and employer (Arocena, Nu´-n˜ez and Villanueva, 2007). Consequently, nowadays we frequently find stable and precarious employment in the same organization (Godin and Kittel, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The current generalized increase in labor insecurity and precariousness affects SMEs (Arocena, Núñez, & Villanueva, 2007). Growing insecurity discredits the labor system, which arises from long-term stability (Cuyper, Van der Heijden, & De Witte, 2011).…”
Section: Stabilitymentioning
confidence: 99%
“…There is also very limited research on the effects of employability on what is a much more analyzed construct, individual task performance. These scarce empirical works suggest that employees with higher employability are more capable of doing their tasks and are more motivated to make an extra effort, so they will receive a better performance appraisal (Arocena et al, 2007;Villanueva, 2005).…”
Section: Employability and Ethical Behaviormentioning
confidence: 99%
“…Along these lines, research by Arocena et al (2007) has shown that employees increase their commitment to the organization when they perceive that firms invest in their employability. As recent research shows, employees may believe that due to current economic dynamics they need to remain organizationally mobile to maintain their job.…”
Section: Employability and Ethical Behaviormentioning
confidence: 99%
See 1 more Smart Citation